2001
DOI: 10.1103/physrevb.65.020507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Al content on the optical phonon spectrum inMg1xAlx

Abstract: Raman and infrared absorption spectra of Mg1−xAlxB2 have been collected for 0 ≤ x ≤ 0.5 in the spectral range of optical phonons. The x-dependence of the peak frequency, the width and the intensity of the observed Raman lines has been carefully analized. A peculiar x-dependence of the optical modes is pointed out for two different Al doping ranges. In particular the onset of the high-doping structural phase previously observed in diffraction measurements is marked by the appearence of new spectral components a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
81
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 22 publications
8
81
0
Order By: Relevance
“…These features have been observed in Al-doped samples and have been associated with structural disorder. [27][28][29] The appearance of more than one phonon peak further implies the violation of Raman selection rules induced by disorder resulting in a modified …”
Section: Full Papermentioning
confidence: 99%
“…These features have been observed in Al-doped samples and have been associated with structural disorder. [27][28][29] The appearance of more than one phonon peak further implies the violation of Raman selection rules induced by disorder resulting in a modified …”
Section: Full Papermentioning
confidence: 99%
“…16,17,18,19 Interband scattering is weak in MgB 2 , 20 but this is not necessarily the case in samples in which Mg has been replaced by Al or B by C (Ref. 21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37) or which have been exposed to neutron irradiation. 38 Such samples exhibit considerably reduced T c , while the two gaps persist even at very low critical temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Going from x=1 to x=0.5 a dramatic increase in the E 2g phonon mode energy ω E2g takes place [29][30][31] increasing from 70 meV to 115 meV as shown in Fig. 2a (from the data in ref.…”
mentioning
confidence: 99%
“…It has been found that the Al 1-x Mg x B 2 alloys [20][21][22][23][24][25][26][27][28][29][30][31] show a continuos evolution through a complicated mixed phase from MgB 2 (x=1) to the end member AlMgB 4 (x=0.5) where a well ordered superlattice structure of boron layers intercalated by alternating layers of Al and Mg is formed [20][21][22][23][24]. In spite of the fact that the alloys with intermediate x are rather disordered, the superconducting transition temperature is still well defined and it drops systematically with decreasing x as shown in Fig.…”
mentioning
confidence: 99%